The Effect of Social Capital on Customer’s Repayment Rate at Islamic Microfinance Institution - Effendi, Jaenal; Utami, Annisa Rindra (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
The potency of Micro and Small Enterprises (MSEs) in Indonesia which is great, is not directly proportional to the ease of getting capital from formal financial institutions such as banks because it is not bankable. Meanwhile, microfinance institutions (MFIs) that provide financing to the MSEs are currently thriving. This condition exposes the existence of factors that cause the MFIs continuesly providing financing to MSEs which are not bankable. This research aims to analyze the effect of social capital toward the repayment rate of Islamic MFIs’ customers. The methods used in this research was the logistic regression. The results showed variable relationship with BMT employees, relations with other customers, and Islamic recitation had positive and significant effect toward the repayment rate of the customer. While recommendations, membership status, and travel time from home to the BMT had negative and significant effect.  Variable outside the social capital indicator which is income rate had no significant effect.DOI: 10.15408/aiq.v8i2.2631